Biology, Computation and Linguistics - Bel-Enguix, Gemma (IOS Press, 2014)
Over time, the root discipline of philosophy separated into many disciplines and sub-disciplines, each of which has developed its own specific methods. Whilst cross-disciplinary interaction between the three vertices of biology, computing and language processing has often occurred quite naturally in the past, these interactions were mostly two-way, because combining more than two disciplines presents significant challenges. But for some disciplines, reaching out to others is no longer a luxury, but a necessity, and an inverse process of integration is now required. Some disciplines have become unnaturally disconnected from others or from the whole, with the result that a broad view is sometimes lost, and parallels which could be exploited to great advantage cannot even be seen. This book presents a series of essays on biology, computation and linguistics. It seeks to make their connectedness more apparent so that these single disciplines, which relate naturally, but which have drifted far apart, can fruitfully reconnect from their present degrees of specialization. Topics covered include: finding isomorphisms between genetic code and verbal language; viewing childhood dialects as modeling computers; the use of a computational formalism - concept formation -for mining both linguistic and biological texts; lower bounds for asymmetrical insertion-deletion languages; a computational model for linguistic complexity; enumerated speculation on possible languages, as well as an exploration of cognitive architectures for multi agent systems from a computational point of view. The book aims to promote further interconnectedness between the humanistic and the formal sciences, for a less dichotomized, more integrated world.